SUSTAINABLE DEVELOPMENT GOALS IN HIGHER EDUCATION INSTITUTIONS: PAST, CURRENT RESEARCH TRENDS AND FUTURE RESEARCH DIRECTION - Rahmadianti, Atikah Bella; Nawanir, Gusman (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
The purpose of this study is to review past, current research trends and predict future research directions. This review uses a bibliometric approach involving 1,787 journal articles retrieved from the Web of Science database. This study conducted co-citation, bibliographic coupling and co-word analyses to determine past, current and future research trends. Past research trends focused on the development of sustainable development goals systems and policies in higher education institutions. In the present, research trends focus on the role of technology, evaluation, and the impact of sustainability transformation in higher education institutions. In the future, this study emphasizes significant changes in education, its impact on the external environment, the creation of sustainability-based curricula and practical skills in higher education institutions. This study will benefit researchers, practitioners and the community by increasing the understanding and implementation of sustainable development goals in higher education institutions.